PENGARUH STRES KERJA TERHADAP KINERJA KARYAWAN DIMEDIASI OLEH KEPUASAN KERJA KARYAWAN PT. DESTINATION ASIA BALI - Diputra, Ade Agus Diama Purwa; Surya, Ida Bagus Ketut (E-Jurnal Manajemen, 2019)
The purpose of this study was to determine and analyze the direct influence of work stress and job satisfaction on employee performance, to determine and analyze the direct effect of work stress on job satisfaction, as well as to know and analyze the effect of job satisfaction in mediating the effect of work stress on employee performance at PT. Destination Asia Bali. The results showed that work stress had a negative and significant effect on job satisfaction and employee performance, job satisfaction had a positive and significant effect on employee performance, job satisfaction positively and significantly mediated the effect of work stress on employee performance. The population in this study were all permanent employees at PT. Destination Asia Bali. Employees remain selected as research population because it is assumed that the employee has more information about the condition of the company. Sampling in this study uses saturated sample or census techniques, so the number of research samples is 56 employees. Data were collected using a questionnaire then analyzed using Path Analysis techniques.